Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1017/s1368980020002116
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of legume consumption related to sociodemographic factors, health status and health-related variables among surveyed adults from Poland

Abstract: Objective: The aims of the study were: (i) to estimate the frequency of legume consumption in a study sample from Poland; (ii) to assess relationships between frequency of legume consumption and sociodemographic factors, health status and health-related variables and (iii) to describe the sociodemographic and health-related profiles of ‘frequent’, ‘rare’ and ‘never legume consumers’. Design: A cross-sectional study with a self-administered questionnaire was conducted. χ2 test compared th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…For instance, part of the meat in familiar dishes could be replaced with legumes. Nutrition professionals should also focus on teaching people how to prepare legumes because inability to cook legumes and lack of knowledge on suitable recipes are common obstacles for legume consumption [ 48 , 49 ]. These kinds of strategies can eventually lead to more sustainable and healthy diets by enhancing the familiarity of legumes and people’s competence to prepare them.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, part of the meat in familiar dishes could be replaced with legumes. Nutrition professionals should also focus on teaching people how to prepare legumes because inability to cook legumes and lack of knowledge on suitable recipes are common obstacles for legume consumption [ 48 , 49 ]. These kinds of strategies can eventually lead to more sustainable and healthy diets by enhancing the familiarity of legumes and people’s competence to prepare them.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are in line with this, as lower education level and financial strain were associated with lower pulse and PBMA consumption. Living area was not strongly associated with pulse and PBMA consumption, even though some earlier research has found that living in large or medium-sized cities often indicates a tendency to consume plant-based foods [e.g., (14)].…”
Section: General Findingsmentioning
confidence: 95%
“…Furthermore, liking the taste of meat, the price of meat alternatives and the routinized nature of meat eating are significant barriers for reducing meat consumption ( 13 ). Skórska et al ( 14 ) discovered that as a large part of Western cooking recipes center around meat, consumers are steered towards meat instead of plant-based protein sources.…”
Section: Applying the Com-b Model In The Context Of Plant-based Eatin...mentioning
confidence: 99%
“…Furthermore legumes are an abundant source of many biologically active compounds, such as vitamins, minerals and phenolic compounds which together present preventive activities against many of the abovementioned disorders. [8,9,10] Unfortunately general legume consumption is low. A study examining frequency of legume consumption among surveyed adults from Poland, described that only 22,8 % of all participants frequent consume legumes and the average consumption amount was approximately 21 g/capita per day in all respondents, and approximately 16 g/capita per day in the non-vegetarian respondents.…”
Section: Introduction and Purposementioning
confidence: 99%
“…Moreover, 'rare legume consumers' declared approximately 7 g/capita per day. [11] The aim of the present review was to analyse the potential benefits of consuming legumes seeds as an efficient strategy to prevent metabolic syndrome and its comorbidities.…”
Section: Introduction and Purposementioning
confidence: 99%